Determinants and Outcomes of Vasoplegia Following Left Ventricular Assist Device Implantation. Issue 11 (22 September 0207) - Tecson, Kristen M.; Lima, Brian; Lee, Andy Y.; Raza, Fayez S.; Ching, Grace; Lee, Cheng‐Han; Felius, Joost; Baxter, Ronald D.; Still, Sasha; Collier, Justin D. G.; Hall, Shelley A.; Joseph, Susan M.
Abstract : Background: Vasoplegia is associated with adverse outcomes following cardiac surgery; however, its impact following left ventricular assist device implantation is largely unexplored. Methods and Results: In 252 consecutive patients receiving a left ventricular assist device, vasoplegia was defined as the occurrence of normal cardiac function and index but with the need for intravenous vasopressors within 48 hours following surgery for >24 hours to maintain a mean arterial pressure >70 mm Hg. We further categorized vasoplegia as none ; mild, requiring 1 vasopressor (vasopressin, norepinephrine, or high‐dose epinephrine [>5 μg/min]); or moderate to severe, requiring ≥2 vasopressors. Predictors of vasoplegia severity were determined using a cumulative logit (ordinal logistic regression) model, and 1‐year mortality was evaluated using competing‐risks survival analysis. In total, 67 (26.6%) patients developed mild vasoplegia and 57 (22.6%) developed moderate to severe vasoplegia. The multivariable model for vasoplegia severity utilized preoperative Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile, central venous pressure, systolic blood pressure, and intraoperative cardiopulmonary bypass time, which yielded an area under the curve of 0.76. Although no significant differences were noted in stroke or pump thrombosis rates ( P =0.87 and P =0.66, respectively), respiratory failure and major bleeding increased with vasoplegia severity ( P <0.01). Those with moderate to severe vasoplegia had a significantly higher risk of mortality than those without vasoplegia (adjusted hazard ratio: 2.12; 95% confidence interval, 1.08–4.18; P =0.03). Conclusions: Vasoplegia is predictive of unfavorable outcomes, including mortality. Risk factors for future research include preoperative INTERMACS profile, central venous pressure, systolic blood pressure, and intraoperative cardiopulmonary bypass time.